Tapering in team sports: Physical performance response in elite rugby sevens players - Marrier, B.; Robineau, J.; Piscione, J.; Peeters, A.; Hausswirth, C.; Morin, J.-B.; Le Meur, Y. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: As for endurance sports, appropriate tapering is considered critical for maximizing team sports performance. However, there is little scientific information available to guide coaches in prescribing efficient tapering strategies for team sports players. The aim of this study was to monitor the changes in physical performance in elite rugby sevens players during a 3-week taper immediately following the pre-season training camp. Methods: 10 male international rugby sevens players were tested before (Pre) and after (Post) a 4-week pre-season training camp, and each week during a subsequent 3-week taper (T1, T2, T3). During each testing session, maximal lower limb strength and explosiveness, sprint acceleration mechanical outputs and performance, and repeated sprint ability were assessed. Results: At Post, both sprint performance and maximal isometric force output remained unchanged, while an almost certain small increase in both mean (MPO) and peak cycling power output (PPO) was reported (+6.0 ± 1.7 % with a 100/0/0 % chance to observe a positive/trivial/negative change in performance and +4.5 ± 2.1 %; 99/1/0 % for MPO and PPO, respectively). During the taper, the 30-meter sprint time improved almost certainly (-3.1 ± 0.9 %, 0/0/100 %, large). A moderate negative correlation (r = -0.50 ± 0.45) between change in sprint running performance and change in Pmax was reported. Maximal force output during the mid-thigh pull improved very likely during the taper (+7.3 ± 6.4 %, 95/3/2 %, small). Both MPO and PPO also improved almost certainly during the same period (+9.0 ± 2.6 %, 100/0/0 %, moderate; 8.6 ± 2.7 %, 100/0/0 %, moderate, respectively). For all variables tested, peak performance occurred on average between 9th and 16th day of taper. Discussion: Although maximal strength, sprint performance and repeated sprint ability kinetics differed, a 2-week tapering timeframe seems optimal to maximize the overall physical performance response in elite rugby sevens players. We also found a substantial inter-individual variability, which supports the importance of an individualized training load during the tapering period.